Classification of Image Corner Point Detection Systems to Identify a Shape - Dadang Iskandar Mulyana; Fiktor Kurnia Tofano (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Study This contains about the detection of circular object images. The circular object tested is the moon image object, the moon image was chosen because the moon image has various moon shapes, namely the full moon, half moon and crescent moon. To detect the shape of the circular object image, several stages are carried out by starting the image segmentation process. (1) The segmentation process using the bi-level thresholding method makes the image black and white, (2) after that the image is repaired with the morphological process of the opening and closing methods. (3) For training data, the shape extraction process is carried out, namely the circular nature of the object (circularity) to determine the roundness of an object. For the testing process, the same process is also carried out as the process of obtaining circular image detection.